Hygienic status of grease proof paper used for food packaging - ΓΙΩΤΗΣ Α.; ΧΑΡΙΣΗΣ Φ.; ΠΑΠΑΝΑΣΤΑΣΙΟΥ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In order to determine the Hygienic Status and demonstrate the acceptability of Grease Proof Paper for Food Packaging, we examined 100 samples of it. It were not found coliforms and coagulase positive staphylococci, whilst total bacterial number was very low. It is deduced that the wide use of Grease Proof Paper does not imply any hazard for the consummer from the point of view of bacterial infection